Avaliação do curso da infecção e da resposta humoral para Anaplasma marginale (Theiler, 1910) em bovinos submetidos ao processo de premunição - Andrea Caetano Silva Loss (1991)
This study was undertaken to evaluate the course of infection by Anaplasma marginale and the immune response in cattle associated with premunization against anaplasmosis. Thirty-nine Limousin cattle, about twenty-four months old, of both sexes, imported from the United States to Capitolio (MG) were used. Animals were alloted to five groups which were infected with Babesia spp and A. marginale. Infections with Babesfa spp were obtained using subcutaneous inoculation of 5x108 infected erythrocytes or by infestation with Boophilus microplus larvae originated from Babesia-infected female ticks. A. marginale infection was attained by subcutaneous inoculation of 5x108 infected erythrocytes simultaneously or seventeen days after animals had been inoculated with Babesia spp. Prepatent period and parasitemia were determinated by examining daily prepared blood smears; packed cell volume (PCV) was weekly determinated by the microhematocrit technique and retal temperature was daily measured twice a day. Treatment was established based on these parameters. Immune response for A. marginale was measured by the indirect fluorescent antibody technique. All animals were challenged with blood infected with A. marginale 56 (two groups) and 73 (three groups) days after inoculation. Although animals had been inoculated with Babesiaspp only data related to A. marginale are presented in this paper. Prepatent period ranged from 19.8 to 26.0 days; mean perasitemia at the beginning of treatment was 2.0% and mean number of treatment/animal varied from 3.2 to 4.4. Lower PCVvalues were found after the peak of parasitemia by A. marginale before and after challenge. Retal temperatures were higher in the afternoon during clinical anaplasmosis. Higher titers of anti-A. marginale antibodies (1:5120) were found 49 days after inoculation. An increase in titers were found up to 48 days after challenge, when the observations were finished.